2019
DOI: 10.1101/834481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primate homologs of mouse cortico-striatal circuits

Abstract: AbstractWith the increasing necessity of animal models in biomedical research, there is a vital need to harmonise findings across species by establishing similarities and differences in rodent and primate neuroanatomy. Using a connectivity fingerprint matching approach, we compared cortico-striatal circuits across humans, non-human primates, and mice using resting state fMRI data in all species. Our results suggest that the connectivity patterns for both the nucleus accumbens a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 89 publications
1
33
0
Order By: Relevance
“…Because of unavailability of pre-symptomatic HD brain tissues, the reasons behind selective striatal vulnerability in HD were mostly investigated using animal models. In fact, the basal ganglia and, particularly, the cortico-striatal motor circuitry, appears to be conserved in mouse, minipig, and primates ( Vodicka et al, 2005 ; Stephenson-Jones et al, 2011 ; Balsters et al, 2020 ). Thus, genetically engineered models, bearing normal or pathological CAG repeat lengths, have revealed important pathogenic mechanisms of the HD mutation ( Menalled, 2005 ; Lerner et al, 2012 ; Peng et al, 2016 ; Table 1 and Figures 1A,B ).…”
Section: Pathogenic Mechanisms Of the Hd Mutation In Striatal Districmentioning
confidence: 99%
“…Because of unavailability of pre-symptomatic HD brain tissues, the reasons behind selective striatal vulnerability in HD were mostly investigated using animal models. In fact, the basal ganglia and, particularly, the cortico-striatal motor circuitry, appears to be conserved in mouse, minipig, and primates ( Vodicka et al, 2005 ; Stephenson-Jones et al, 2011 ; Balsters et al, 2020 ). Thus, genetically engineered models, bearing normal or pathological CAG repeat lengths, have revealed important pathogenic mechanisms of the HD mutation ( Menalled, 2005 ; Lerner et al, 2012 ; Peng et al, 2016 ; Table 1 and Figures 1A,B ).…”
Section: Pathogenic Mechanisms Of the Hd Mutation In Striatal Districmentioning
confidence: 99%
“…Second, such work is a key translational link across species (i.e. rodents to humans), given the common use of neuroimaging readouts from rsfMRI ( Balsters et al, 2020 ). At the genomic level we then examine what cell types could possibly underlie sex-related heterogeneity in E:I imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Similar interspecies microanatomical features and whole-brain axonal projection patterns of subareas in the primate Acb have been qualitatively described (Rigoard et al, 2011; Wedeen et al, 2012; Jbabdi et al, 2013; Balsters et al, 2019), and evolutionarily conserved functions have been suggested for them (Izawa et al, 2003; Calipari et al, 2012; Daniel and Pollmann, 2014) and used as a priori knowledge for further studies (Neubert et al, 2015; Heilbronner et al, 2016). However, whether these conserved functions are supported by macroscopic structural connectivity given the disproportionate volumetric changes during primate evolution in the brain regions that project to the Acb (Carlén, 2017; Smaers et al, 2017) and the prefrontal white matter (Schoenemann et al, 2005) has not been established.…”
Section: Introductionmentioning
confidence: 61%
“…Many evolutionarily conserved structural and functional features of the subcortical structures, including the Acb, have been suggested (Izawa et al, 2003; Calipari et al, 2012; Daniel and Pollmann, 2014; Balsters et al, 2019) and used as a priori knowledge (Heilbronner et al, 2016; Neubert et al, 2015). But researchers have also pointed out that many of their features had changed because of their different evolutionary paths.…”
Section: Discussionmentioning
confidence: 99%